Interest rate pass-through : empirical evidence for Barbados - Mamingi, Nandu (Central Bank of Barbados [St. Michael]BB, 2008)
Investigates the effectiveness of central bank's interest rate policy (minimum deposit rate) on commercial bank's lending rate behaviour in Barbados for the period 1980 to 2007.